2008
DOI: 10.1109/tsmca.2008.2001070
|View full text |Cite
|
Sign up to set email alerts
|

Queuing Network Modeling of a Real-Time Psychophysiological Index of Mental Workload—P300 in Event-Related Potential (ERP)

Abstract: Modeling and predicting of mental workload are among the most important issues in studying human performance in complex systems. Ample research has shown that the amplitude of the P300 component of event-related potential (ERP) is an effective real-time index of mental workload, yet no computational model exists that is able to account for the change of P300 amplitude in dual-task conditions compared with that in single-task situations. We describe the successful extension and application of a new computationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 73 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…The distraction of the movie might have changed the manner in which the children processed the auditory stimuli. Decreased P300 amplitudes have been related to difficulty discriminating stimuli (Sugawara et al, 1994) and increased task difficulty (Wu et al, 2008) and, in general, are smaller in people with disabilities (Linden, 2005). In our study, having the children watch a movie could have distracted them from listening to the auditory stimuli.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The distraction of the movie might have changed the manner in which the children processed the auditory stimuli. Decreased P300 amplitudes have been related to difficulty discriminating stimuli (Sugawara et al, 1994) and increased task difficulty (Wu et al, 2008) and, in general, are smaller in people with disabilities (Linden, 2005). In our study, having the children watch a movie could have distracted them from listening to the auditory stimuli.…”
Section: Discussionmentioning
confidence: 59%
“…This late component is indicative of additional cognitive activity (Polich, 2007). P300 has become the most studied ERP component (Wu, Liu, & Quinn-Walsh, 2008). Other P300 research has found significant differences between neurotypical individuals and individuals with schizophrenia (Klein, Berg, Rockstroh, & Andresen, 1999;Weisbrod, Hill, Niethammer, & Sauer, 1999), attention deficit hyperactivity disorder (Barry, Johnstone, & Clarke, 2003;Sugawara, Sadeghpour, Traversay, & Ornitz, 1994;Sunohara et al, 1999), autism (Lincoln, Courchesne, Harms, & Allen, 1995), and epilepsy (Naganuma et al, 1997).…”
mentioning
confidence: 99%